Induction of antigen‐positive cell death by the expression of Perforin, but not DTa, from a DNA vaccine enhances the immune response. Issue 4 (10th December 2013) - Gargett, Tessa; Grubor‐Bauk, Branka; Garrod, Tamsin J; Yu, Wenbo; Miller, Darren; Major, Lee; Wesselingh, Steve; Suhrbier, Andreas; Gowans, Eric J
Abstract : The failure of traditional protein‐based vaccines to prevent infection by viruses such as HIV or hepatitis C highlights the need for novel vaccine strategies. DNA vaccines have shown promise in small animal models, and are effective at generating anti‐viral T cell‐mediated immune responses; however, they have proved to be poorly immunogenic in clinical trials. We propose that the induction of necrosis will enhance the immune response to vaccine antigens encoded by DNA vaccines, as necrotic cells are known to release a range of intracellular factors that lead to dendritic cell (DC) activation and enhanced cross‐presentation of antigen. Here we provide evidence that induction of cell death in DNA vaccine‐targeted cells provides an adjuvant effect following intradermal vaccination of mice; however, this enhancement of the immune response is dependent on both the mechanism and timing of cell death after antigen expression. We report that a DNA vaccine encoding the cytolytic protein, perforin, resulted in DC activation, enhanced broad and multifunctional CD8 T‐cell responses to the HIV‐1 antigen GAG and reduced viral load following challenge with a chimeric virus, EcoHIV, compared with the canonical GAG DNA vaccine. This effect was not observed for a DNA vaccine encoding an apoptosis‐inducing toxin, DTa, or when the level of perforin expression was increased to induce cell death sooner after vaccination. Thus, inducing lytic cell death following a threshold level of expression of a viral antigen can improve the immunogenicity of DNA vaccines, whereas apoptotic cell death has an inhibitory effect on the immune response.